Tinjauan Aplikasi Piranti Rel Penyeberang Orang (Piren) Berdasarkan Observasi Dan Persepsi Penyeberang Jalan - Romadhona, Prima Juanita (Warta Penelitian Perhubungan, 2010)
Densihj of traffic flow in lnrge dties in Indonesin at present has become a big issue; congestion on themain street has become n regulnr tlzing e7.ien1 dmj, especinlly dunÂ·ng the peak hours. Tizis situation ledt.o the pedestrian difficult to cross the road, for example in sclzools in the arterial roads and collectorstreets, pedestrian activihJ sometimes walked chaotic and often 1iehicles do not comply with signs inpedestrian areas so that many acddent cases. Tiiis stud!.; tried t.o review the condition of road userbehavior with the implementation of the Pedestrian Rail Tool (PIREN) which is a tool that thepedestrian crossing is designed to prmnde convenience and safehJ for the pedestrian so it can reducethe number of mctims of acddents while crossing the street. Tire research approach is biJ observationof pedestrian road crossing speeds and long waiting times witlwut and 11rith using PIREN andreaction from pedestrian about PIREN l1J7Plicntlo11 7l'ith the help of questionnaire and then analyzedbij using Importance Perfommnce Analysis metlwd.From 73 PIREN users, appreciating that PIREN can be ne7.U tech tools that make more secure andsafe wlren crossing, but there are still some perfimnance fact.ors that need t.o be improved. Based on thecartesius diagram obtained 2 indicators in quadrant A which are tire main priorihJ for improvedservices, 4 indicators are in tire quadrant B which are perfommnce le7.iels should be maintained, 1indicator is in quadrant C, which is an indimtor of low prionÂ·hJ and 3 indicators in quadrant D thatperformance le7.:iels is excessi11e.Keywords: Pedestrian, PIREN, Importance Perfonnance Analysis